The Most Important Bio-movement Abilities and its Correlation to the Performance of the Skill of Forehand Jump on the Surface of Movements for the Women's Gymnastic - Ruaa Ali Hussein (Journal of Global Pharma Technology, 2018)
The researchers, according to the nature of the educational process of the basic skills in the gymnastic noted the weakness of the capabilities in the performance of the performance of the players of the Faculty of Education for Girls University of Kufa, especially in the performance of the skill of the leap of the front hands on the ground movements of women, Therefore, the researchers sought to study the relationship between the most important bio movement abilities and the performance of the skill of the frontal leap on the surface of the movements of the ground in the women's gymnastics. The descriptive approach was chosen in the method of correlative relations to suit the nature of the research problem. The research community was (10) Kufa. The first experiment was conducted first and then the main experiment of the research procedures was conducted. The results that were dealt with were obtained using the statistical file (SPSS) which enabled the researchers to reach the conclusion that there is a positive correlation between the more bioethics (flexibility, compatibility, explosive arm force, and balance), the better the performance is for the better. The recommendations are the need to pay attention to the training of the bio movement abilities of the various sporting events.Keywords: Bio-movement, Performance, Surface of movement’s and gymnastic